Early childhood development coming of age: science through the life course. Issue 10064 (7th January 2017) - Black, Maureen M; Walker, Susan P; Fernald, Lia C H; Andersen, Christopher T; DiGirolamo, Ann M; Lu, Chunling; McCoy, Dana C; Fink, Günther; Shawar, Yusra R; Shiffman, Jeremy; Devercelli, Amanda E; Wodon, Quentin T; et al.
Summary: Early childhood development programmes vary in coordination and quality, with inadequate and inequitable access, especially for children younger than 3 years. New estimates, based on proxy measures of stunting and poverty, indicate that 250 million children (43%) younger than 5 years in low-income and middle-income countries are at risk of not reaching their developmental potential. There is therefore an urgent need to increase multisectoral coverage of quality programming that incorporates health, nutrition, security and safety, responsive caregiving, and early learning. Equitable early childhood policies and programmes are crucial for meeting Sustainable Development Goals, and for children to develop the intellectual skills, creativity, and wellbeing required to become healthy and productive adults. In this paper, the first in a three part Series on early childhood development, we examine recent scientific progress and global commitments to early childhood development. Research, programmes, and policies have advanced substantially since 2000, with new neuroscientific evidence linking early adversity and nurturing care with brain development and function throughout the life course.